Culture. Science. Education: modern trends - Vinokurov A. A., Nabokova L. S., Khalina N. V., Anikin D. V., Valiulina E. V., Dorokhov N. I., Stepanova T. I., Tselishcheva Z. A., Kuznetsova E. V., Bezgodov A. V., Kurasova E. A., Kurasova E. A., Stenkina E. N., Savitskaya E. V., Kostenko E. G., Lysenko V. V., Saikina G. K., Kadnikova O. I., Altynbaeva G. K., Aidarkhanov A. M., Toretaev M. O., Valiulin R. R., Valiulina E. V., Sukhomlina T. A., Kasianenko T. G., Vorotilkina A. M., Sergeev T. S., Alisin V. V., Svinukhov V. G., Senotrusova S. V., Zhoglicheva V. V., Tesalovskaia V. E., Sovetova N. P., Aksiutina S. V., Dosbenbetova A. S., Abramova G. I., Iumasheva E. V., Stashkov V. B., Anishchenko N. D., Pospelov A. A., Rozanov K. I., Kolovanov O. A., Dylevskaia L. A., Sovetova N. P., Chaika N. M., Pavliuk T. P. (Culture. Science. Education: modern trends, 2020)
the main aspects of the interrelation of illustrating the text and methods of their perception are revealed in the article. For a more convincing and full-fledged visualization of a literary work, a comprehensive and in-depth study of episodes of the text is necessary. The purpose of the article is to identify the interrelation between the visual arts and philology – the methods and form of studying a literary work for its further illustration. In connection with this the following tasks were set out: 1) to identify the main methods and ways of a literary work perception; 2) to analyze and compare specific ways of illustration; 3) identify the features of book design creation. The following features of illustration were revealed during the study: its interrelation with the text, functions of replenishment and explanations, the influence of visual perception, integrity and semantic logic of creating drawings for text, taking into account the purpose of illustration (age, scientific character, visibility, etc.), the use of appropriate technology of illustration.
Keywords: восприятие; Perception; иллюстрация; illustration; литературное произведение; визуальный ряд; книжная графика; эмоционально-ассоциативное мышление; архитектоника книги; literary work; visual series; book graphics; emotional and associative thinking; architectonics of the book